Being at work : using existentialism to make sense of your organisational life - Cole, Mark (Routledge, 2026)
This thought-provoking and ground-breaking book offers a way for us all to consider our experience of being at work, and of the nature of working life. Written in an engaging and accessible style, it presents the practical means by which to apply central features of existentialism to make sense of how we relate to work and the workplace.These include topics such as freedom and choice, looking for purpose and making meaning, and authenticity. We spend a great deal of time at work, and being at work is often a challenge. Reference to the past in a corporate context tends to see it as a graveyard for errors and failures; the future is something articulated by senior leaders and the place to which we are expected to travel, in terms of their definition. The (specious) present is the place where we experience our being in the moment, the location where we do our work but it is rarely acknowledged in the places where we work. This book offers new insights into how we can all meaningfully live our lives in the context of the world of work. To do this, it offers a personalised understanding of the existentialist way of philosophising. It looks to simplify complex concepts in order to offer the reader a different way of thinking about the time that they spend at work and how they might consider different and more positive ways of being in such an environment. It recognises that we spend a considerable amount of our life in the workplace - and so argues that we need to consider that and find ways in which to make that experience personally meaningful.Where other practices designed to help people to make sense of their actual experience are introspective, existentialism is reflexive and active. Similarly, where those other approaches are deeply individualistic, existentialism constantly reminds us that our choices are undertaken in relation to others and that they have a collective implication. Whether you are keen to make sense of your experience of workplace - and what it means to be a human being in that context - or looking to explore how you embrace the challenges of being a leader in business, this book will offer you rich perspectives for sense making and ways of rethinking your presence at work.
Keywords: Existentialism.; Work environment.; elektronické knihy; electronic books